Multimodal Discourse Analysis of Religious Tourism on Madura Island, Indonesia - Ekawati, Rosyida; Puspitasari, Desi; Hanifa, Siti (Institut Pariwisata dan Bisnis Internasional, 2021)
The objective of study is to explore the relationship between visual and verbal elements within the frame of multimodal discourse analysis in Madura tourism promotion. Promotion in the form of moving images with verbal language makes it easier for readers and potential tourists to see tourist attractions more closely and realistically. This study is descriptive qualitative using 3 videos of Madura tourism promotion, in particular tourism promotions of Bangkalan, Pamekasan, and Sampang regencies on Madura Island, Indonesia. Only scene representing religious tourism as the data of this study in which there are 8 data of religious tourism images. There are two parts of data analysis: visual and verbal analyses. Visual semiotic mode of scenes and images were analyzed using visual grammar by Kress and van Leeuwen (2006). In addition, verbal data are all of utterances generated during the scenes and the still images were analyzed based on appraisal framework by Martin and White (2005) especially on the attitude system. Results show that tourism promotional videos use more than one mode of communication or semiotic system elements to create meaning through representational and interactive structures, compositional meanings, and verbal language. All of the compositions can come together to create messages to the public, in this case information about tourist attractions and their locations that represent the religiosity of Madura.